RUANG - Mr. Syafrinaldi (SURYA SENI, 2008)
“Space” is a choreography inspiration by a story Pendam Tujuh of Kerajaan Kingdom in Riau Province. Pendam Tujuh  means in ground keeping ground. It tells about seven girl who are kept in gound because of their act of disseminating information about the out-of marriage pregnancy of Batin Betina(a governor in Keritang Kingdom). The story is passed on orally among Riau people. The choreographer sees the story in comparison with the present condition of prisoners. They are imprisoned because of certain guilt and must live in a jail. The author got the idea of the creation a year ago when he saw the occurrences taking place amidst the people. When we observe, there are many news in television and magazine about violence, drugs abuse, robbery, rape, riots, and murderthat inﬂ ict a loss on others and on the criminals. The criminals are punished in jail because of the guilt, they committiet. The “Space” consideret to be a chorographical exposure is interpreted to be a violence space in the attitude andbehavior with the burying spirit. It means that whoever is in the burying space or the jail, he or she will be fettered, conﬁ ned and loss the space to have certain attitude and behavior as decent human being.Keywords: Pendam Tujuh and space.